2012
DOI: 10.1371/journal.pone.0045949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SNPs on Creatine Kinase Structure and Function: Identifying Potential Molecular Mechanisms for Possible Creatine Kinase Deficiency Diseases

Abstract: Single-nucleotide polymorphisms (SNPs) are common genetic material changes that often occur naturally. SNPs can cause amino acid replacements that may lead to severe diseases, such as the well-known sickle-cell anemia. We constructed eight SNP mutants of human brain-type creatine kinase (CKB) based on bioinformatics predictions. The biochemical and biophysical characteristics of these SNP mutants were determined and compared to those of the wild-type creatine kinase to explore the potential molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Most of the identified non-synonymous variants in the genes of interest were predicted to impact the protein structure. Previously, alterations in the biochemical and biophysical properties of CKB caused by distinct genetic variations leading to amino acid substitutions have been analyzed ( Li et al, 2012 ). Eight non-synonymous variants in CKB were studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the identified non-synonymous variants in the genes of interest were predicted to impact the protein structure. Previously, alterations in the biochemical and biophysical properties of CKB caused by distinct genetic variations leading to amino acid substitutions have been analyzed ( Li et al, 2012 ). Eight non-synonymous variants in CKB were studied.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that half of the variants’ amino acid substitutions affected the catalytic efficiency. For instance, the resultant amino acid exchange of rs13558 (p.Lys267GLu) increases the enzymatic activity by ∼ 30% compared to CKB containing the wild-type lysine ( Li et al, 2012 ). Further amino acid substitution due to other SNP alleles conversely impaired the catalytic efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asp-63 is among the residues that are predicted to be subjected to N-linked glycosylation. The amino acid is located in the 60-70 flexible loop [Bong et al, 2008;Li et al, 2012;McLeish and Kenyon, 2005]. Due to the high importance of the loop in catalysis, such glycosylation may decrease its flexibility and may reduce the activity.…”
Section: Hckmbt Displayed Superior Specific Activitymentioning
confidence: 99%